Chemical Synthesis of A Pore‐Forming Antimicrobial Protein, Caenopore‐5, by Using Native Chemical Ligation at a Glu‐Cys Site. Issue 2 (25th November 2014) - Medini, Karima; Harris, Paul W. R.; Hards, Kiel; Dingley, Andrew J.; Cook, Gregory M.; Brimble, Margaret A.
Abstract The 2014 report from the World Health Organization (WHO) on antimicrobial resistance revealed an alarming rise in antibiotic resistance all around the world. Unlike classical antibiotics, with the exception of a few species, no acquired resistance towards antimicrobial peptides (AMPs) has been reported. Therefore, AMPs represent leads for the development of novel antibiotics. Caenopore‐5 is constitutively expressed in the intestine of the nematode Caenorhabditis elegans and is a pore‐forming AMP. The protein (82 amino acids) was successfully synthesised by using Boc solid‐phase peptide synthesis and native chemical ligation. No γ‐linked by‐product was observed despite the use of a C‐terminal Glu‐thioester. The folding of the synthetic protein was confirmed by 1H NMR spectroscopy and circular dichroism and compared with data recorded for recombinant caenopore‐5. The permeabilisation activities of the protein and of shortened analogues were evaluated.